Impact of anemia on long‐term outcomes after percutaneous coronary intervention for chronic total occlusion. Issue 2 (11th November 2017) - Stähli, Barbara E.; Gebhard, Cathérine; Gick, Michael; Ferenc, Miroslaw; Mashayekhi, Kambis; Buettner, Heinz Joachim; Neumann, Franz‐Josef; Toma, Aurel
Abstract: Objectives: A single‐centre, observational study was performed in order to investigate the relationship between anemia and outcomes after percutaneous coronary intervention (PCI) for chronic total occlusion (CTO). Background: Anemia has been identified as adverse predictor in patients with coronary artery disease undergoing coronary revascularization. Data on the impact of anemia on outcomes in patients undergoing PCI for CTO lesions are lacking. Methods: A total of 1, 964 patients undergoing CTO PCI were stratified according to the presence/absence of anemia (hemoglobin of <13 g/dl for men and <12 g/dl for women). The primary endpoint was all‐cause mortality. Median follow‐up was 2.6 (interquartile range 1.1‐3.1) years. Results: Of the 1, 964 patients, 297 (15.1%) had anemia. Anemic as compared to nonanemic patients had and an increased all‐cause mortality (27.9% versus 9.1%, P < 0.001), and associations remained significant after multivariable adjustments (adjusted HR 2.26, 95% CI 1.71‐2.98, P < 0.001). All‐cause mortality decreased with increasing hemoglobin tertiles (T1: 18.6%, T2: 8.6%, T3: 8.2%, log rank P < 0.001). Procedural success was associated with reduced all‐cause mortality both in anemic (21.8% versus 47.2%, adjusted HR 0.59, 95% CI 0.37‐0.93, P = 0.02) and nonanemic patients (7.8% versus 16.3%, adjusted HR 0.64, 95% CI 0.42‐0.98, P = 0.02, interaction P = 0.69). Conclusions: Although anemia is associated with an increased all‐cause mortality in patients undergoing CTO PCI, the survival benefit associated with successful CTO recanalization is maintained.